The Effect of Growth Regulatory Substances (ZPT) and Liquid Organic Fertilizer (POC) Conch Mas (Pamocea canaliculata L.) on Growth and Production of Green Mustard (Brassica juncea L) - Nurul Aliyatil Fachiroh; Abdul Wachid (Universitas Muhammadiyah Sidoarjo, 2016)
This study aims to determine the effect of the dose of liquid organic fertilizer (POC) goldensnail and duration of soaking on growth and yield green mustard plants (Brassica junceeL). The study was conducted in Patuk Village Gempol District, Pasuruan Regency, fromJune to July 2014. Research this was factorially arranged using a randomized blockdesign (RBD) consisting of 2 factors 1 is the administration of liquid organic fertilizer (POC)golden snail consisting of: without POC (D0), dose of 10cc / liter (D1), dose 20cc / liter(D2), dose of 30cc / liter (D3). Factor 2 is the duration of the ZPT immersion consistsof: without immersion (P1), 10 minutes immersion (P2), immersion 30 minute (P3). Fromthese two factors, 12 combinations were obtained and repeated 3 times. The resultsshowed that administering a dose of fertilizer liquid organic (POC) gold snail 20cc / literand a soaking time of 10 minutes (D2P2) give good results on variable plant height,number of leaves, diameter stem, leaf area, wet weight and dry weight.